The Effectiveness and Safety of Stereotactic Body Radiation Therapy (SBRT) in the Treatment of Oligoprogressive Breast Cancer: A Systematic Review - Bernie Yan; Sherif Ramadan; Katarzyna J. Jerzak; Alexander V. Louie; Elysia Donovan (Current Oncology, 2023)
Stereotactic body radiotherapy (SBRT) has emerged as a technique to treat oligoprogressive sites among patients with breast cancer who are otherwise doing well on systemic therapy. This study systematically reviewed the efficacy and safety of SBRT in the setting of oligoprogressive breast cancer. A literature search was conducted in the MEDLINE database. Studies regarding SBRT and oligoprogressive breast cancer were included. Key outcomes of interest were toxicity, local control, progression, and overall survival. From 863 references, five retrospective single-center cohort studies were identified. All studies included patients with both oligometastatic and oligoprogressive disease; 112 patients with oligoprogressive breast cancer were identified across these studies. Patient age ranged from 22 to 84, with a median of 55 years of age. Most patients had hormone-receptor-positive and HER2-negative disease. SBRT doses varied from 24 to 60 Gy in 1–10 fractions based on the location/size of the lesion. Forty toxicity events were reported, of which the majority (n = 25, 62.5%) were grade 1–2 events. Among 15 patients who received SBRT concurrently with a CDK4/6 inhibitor, 37.5% of patients experienced grade 3–5 toxicities. Progression-free and overall survival ranged from 17 to 57% and 62 to 91%, respectively. There are limited data on the role of SBRT in oligoprogressive breast cancer, and prospective evaluation of this strategy is awaited to inform its safety and efficacy.